Kasus Tabrak Lari Suatu Tinjauan Sosiologi Hukum - Sriwati Sakkirang (Al-'Adl, 2008)
If there are events about traffic accidents where the abuser is not to be judged alone because the hit and crashed is a human being in the eyes of God and the same Law. Where they are victims also who need help soon, let us take them to the nearest hospital and then afterward to the police station to resolve the issue. If so, then the case of hit-and-run will not happen, God willing